2018
DOI: 10.1177/1357633x18796439
|View full text |Cite
|
Sign up to set email alerts
|

Impact of telemedicine on the clinical outcomes and healthcare costs of patients with chronic heart failure and mid-range or preserved ejection fraction managed in a multidisciplinary chronic heart failure programme: A sub-analysis of the iCOR randomized trial

Abstract: Background The efficacy of telemedicine in the management of patients with chronic heart failure and left ventricular ejection fraction ≥40% is poorly understood. The aim of our analysis was to evaluate the efficacy of a telemedicine-based intervention specifically in these patients, as compared to standard of care alone. Methods The Insuficiència Cardiaca Optimització Remota (iCOR) study was a single centre, randomised, controlled trial, designed to evaluate a telemedicine intervention added to an existing ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 24 publications
2
46
0
1
Order By: Relevance
“…Frederix et al 48 reported insignificant long-term savings of approximately 27% from an initial 6 month telehealthcare intervention. Jiménez-Marrero et al 49 report savings of approximately 38% for a subgroup of HF patients with a left ventricular ejection fraction >40. Comín-Colet et al 50 report savings of approximately 45%, mainly driven by a significant reduction in hospitalisations between the telehealthcare group and control group.…”
Section: Discussionmentioning
confidence: 99%
“…Frederix et al 48 reported insignificant long-term savings of approximately 27% from an initial 6 month telehealthcare intervention. Jiménez-Marrero et al 49 report savings of approximately 38% for a subgroup of HF patients with a left ventricular ejection fraction >40. Comín-Colet et al 50 report savings of approximately 45%, mainly driven by a significant reduction in hospitalisations between the telehealthcare group and control group.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast with usual HF programme models, where only highly selected patients are candidates to be managed in hospital‐based units and delivery of care is based on face‐to‐face encounters, these new remote management transitional care models delivered using mHealth platforms allow extending a high standard of care to real‐world patients who are often expelled from specialized hospital care. Interestingly, in our previous study, we showed that the efficacy of TM combining telemonitoring and teleintervention was similar in all patients regardless of age, frailty, co‐morbidities, and ejection fraction 7,13 . This approach will reduce patient inequalities in access to good quality of care.…”
Section: Discussionmentioning
confidence: 75%
“…Particularly, combining, from one side, teleintervention by VC to deliver structured pre‐planned interventions and, from the other side, telemonitoring of signs and symptoms, may be an effective strategy especially for those patients with HF in the so‐called ‘vulnerable phase’ , the period that encompasses discharge from an acute HF admission and the following early post‐discharge period. Besides, from the subgroup analyses of the iCOR study, 7 we believe that the benefit will extend to all HF patients in the ‘vulnerable phase’ regardless of LVEF, 13 presence of frailty, depressive symptoms, or co‐morbidities. The purpose of the HERMeS trial will also include validation of the main results of the iCOR study in a nationwide ‘vulnerable phase’ HF patient's cohort and confirm the robustness of the results among different clinical subgroups of patients and diverse health care settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study on the effectiveness of nurse-led telemedicine teams in a regional healthcare system showed a significant decrease across several acute stroke metrics (Fowler et al, in press). Additional evidence shows rural health systems can reduce patient mortality while reducing costs (Siwicki, 2018), help patients and clinicians more effectively manage chronic diseases, such as diabetes and chronic heart failure (Kim, Park, Lee, Jung, & Park, 2018;Jiménez-Marrero et al, 2018), and use mental health technologies that have considerable promise (Wozney et al, 2018).…”
Section: Telehealthmentioning
confidence: 99%